2023
DOI: 10.18178/ijiet.2023.13.2.1797
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Meta-UI in AR and VR Application for Medical Education

Abstract: Immersive technology has provided many benefits in various fields, including in medical education. Several learning obstacles have been overcome, such as limited practicum space, few teaching aids, and limited time. To address this issue further, the authors are building virtualized AR and VR modules that are implemented to help users improve their skills before doing practical work in the real world. The authors use AR technology to study human anatomy, while VR technology to study Normal Childbirth Surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…They developed a conceptual framework and conducted user research to assess the effectiveness of the diegetic approach on user engagement and comprehension. Fajrianti et al [31] studied the effectiveness of meta-UI (meta-user interface) in educational AR and VR apps for medicine. Through user trials, they found that incorporating meta-UI features significantly improves user engagement, task performance, and learning efficacy.…”
Section: A the Current Immersive Research On Evaluating Usermentioning
confidence: 99%
“…They developed a conceptual framework and conducted user research to assess the effectiveness of the diegetic approach on user engagement and comprehension. Fajrianti et al [31] studied the effectiveness of meta-UI (meta-user interface) in educational AR and VR apps for medicine. Through user trials, they found that incorporating meta-UI features significantly improves user engagement, task performance, and learning efficacy.…”
Section: A the Current Immersive Research On Evaluating Usermentioning
confidence: 99%